2011
DOI: 10.1037/a0022985
|View full text |Cite
|
Sign up to set email alerts
|

Is authoritative teaching beneficial for all students? A multi-level model of the effects of teaching style on interest and achievement.

Abstract: This study examined the effects of the two facets of authoritative teaching-high academic press and caring for students-on student interest and achievement in mathematics for middle and high school students (N ϭ 3,602 in 198 classrooms), and whether those effects are moderated by students' ethnicity (Hispanic, Vietnamese, and Caucasian Non-Hispanic). Tested with hierarchical modeling, a trend suggested that the authoritative teaching style predicted higher levels of interest for Hispanic students; however, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 51 publications
1
53
0
Order By: Relevance
“…Baurmind stated that the presence of authoritative parents result in the, "most positive outcomes" both psychologically and academically. This view is shared by Dever and Karabenick (2011), who found that children who constantly had authoritative parents were intrinsically motivated, and high achieving in school. Similar findings were reported for parenting styles across different cultures, including the Arabic culture (Aldhafri, 2011;Assadi et al, 2007;Besharat et al, 2011;Cheung & McBride-Chang, 2008;Gonzalez, Holbein, & Quilter, 2002;Turner, Chadler, & Heffer, 2009).…”
Section: Teaching Stylesmentioning
confidence: 92%
See 2 more Smart Citations
“…Baurmind stated that the presence of authoritative parents result in the, "most positive outcomes" both psychologically and academically. This view is shared by Dever and Karabenick (2011), who found that children who constantly had authoritative parents were intrinsically motivated, and high achieving in school. Similar findings were reported for parenting styles across different cultures, including the Arabic culture (Aldhafri, 2011;Assadi et al, 2007;Besharat et al, 2011;Cheung & McBride-Chang, 2008;Gonzalez, Holbein, & Quilter, 2002;Turner, Chadler, & Heffer, 2009).…”
Section: Teaching Stylesmentioning
confidence: 92%
“…Many researchers have identified these styles as corresponding to those found in the parenting literature. Dever and Karabenick (2011) defined parenting styles according to Baumrind's two dimensions: responsiveness and demandingness. Responsiveness involves warmth, care, and meeting individual needs, while demandingness involves high expectations, strong behavioral control, and autonomy support.…”
Section: Teaching Stylesmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers' interaction styles, in turn, were measured in daily learning situations with a particular student. Three dimensions of teachers' interactional styles (see also Dever & Karabenick, ; Kiuru et al., ; Walker, ), adapted from the literature on parenting style (Aunola & Nurmi, ; Baumrind, ; Walker, ), were used: affection, behavioral control, and psychological control. Affection refers to the extent to which the teacher shows warmth, acceptance, and involvement when interacting with the child.…”
Section: Temperament and Academic Skill Developmentmentioning
confidence: 99%
“…Similarly, of note is that AW is viewed differently across cultures; such variations in perceptions of child behavior could play a role in how parents respond to AW behavior (e.g., Dever & Karabenick, 2011). Third, interpersonal differences between teachers, such as their own level of shyness, have also been found to play a role in their evaluation of children who display high levels of AW (Coplan et al, 2011).…”
Section: Limitationsmentioning
confidence: 99%